The relationship on conflict handling styles and job performance among employees: a case study at Jabatan Kesihatan Negeri Sarawak, Kuching Division / Nur-Amalina Buseman - Buseman, Nur-Amalina (2016)
The purpose of this study was to identify which element of conflict handling styles has the highest level of contribution towards job performance and also to determine the relationship between conflict handling styles and job performance. Conflict handling styles was measured by the Thomas-Kilmann MODE instrument. For any organization, in order to be effective there must have a sufficient conflict handling styles that effect on the employee’s job performance. In addition, this study provides an important insight into various strategies of conflict handlings styles towards employee’s job performance. This study used a quantitative method which was a questionnaire that was distributed to 103 respondents. Besides, Descriptive and Correlation analysis was used for this study to examine conflict handling styles and employee’s job performance. The findings showed the highest contribution of conflict handling styles on employee’s job performance was competing style. The strongest relationship between conflict handling styles and job performance was accommodating style. The results of the findings also supported the hypothesis. Evidence provided in this study supports how employees manage conflict handling styles towards their job performance in the organization. Further research for this study was necessary by involving private sector to enhance the researcher understanding the conflict handling styles and job performance.